Neighbourhood deprivation and cardiometabolic outcomes in the UK Biobank: differences by sex and ethnicity - Véronique L Roger; Katsuyuki Miura; Yangyang Deng; Mohammad Moniruzzaman; Kosuke Tamura; Ram Jagannathan; Lu Hu; Leonardo Mariño-Ramírez; Breanna Rogers (Open Heart)
Objective To examine the associations of deprived neighbourhoods with all-cause mortality and incident cardiovascular disease (CVD) and to investigate whether these associations were independently and concurrently stratified by sex and ethnicity.Methods Data came from the UK Biobank, a prospective cohort study of over 500 000 participants aged 22–69 across the UK between 2006 and 2010. The follow-up time was calculated from each participant’s enrolment at baseline until the first occurrence of a diagnosis of each death, incident or the censor date (31 December 2020). All-cause mortality, incident total CVD, ischaemic heart disease (IHD) and cerebrovascular disease (CeVD) were the outcomes defined based on the International Classification of Diseases. Deprived neighbourhoods were categorised into four groups: least deprived (referent), somewhat deprived, deprived, and most deprived neighbourhoods. Cox proportional hazards models were used to examine associations of deprived neighbourhoods with each outcome. Analyses were stratified by sex and ethnicity separately and simultaneously.Results A total of 261 954 participants were included. Participants had a mean follow-up of 14.3 years for all-cause mortality (3 745 307 person-years, 9933 deaths) and 12.7 years for total CVD incidence (3 321 619 person-years, 64 748 events). Those in the most deprived neighbourhoods (compared with the least) had a 31%, 13%, 15% and 34% greater risk of all-cause mortality, incident total CVD, IHD and CeVD, respectively. Patterns of associations were somewhat similar by sex, yet varied by ethnicity. The overall results were consistent with the white cohort but not for the other cohorts.Conclusions This study indicated that individuals living in highly deprived neighbourhoods may have an elevated risk of all-cause mortality and incident CVD, particularly among the white cohort but not other cohorts. Future research should focus on efforts to invest in deprived areas to alleviate the burden of all-cause mortality and CVD incidence.